Deep Intronic Sequence Variants in COL2A1 Affect the Alternative Splicing Efficiency of Exon 2, and May Confer a Risk for Rhegmatogenous Retinal Detachment. Issue 10 (21st August 2016) - Spickett, Carl; Hysi, Pirro; Hammond, Chistopher J; Prescott, Alan; Fincham, Gregory S; Poulson, Arabella V; McNinch, Annie M; Richards, Allan J; Snead, Martin P
Abstract : Fundus photograph of superior bullous rhegmatogenous retinal detachment. ABSTRACT: COL2A1 mutations causing haploinsufficiency of type II collagen cause type 1 Stickler syndrome that has a high risk of retinal detachment and failure of the vitreous to develop normally. Exon 2 of COL2A1 is alternatively spliced, expressed in the eye but not in mature cartilage and encodes a region that binds growth factors TGFβ1 and BMP‐2. We investigated how both an apparently de novo variant and a polymorphism in intron 2 altered the efficiency of COL2A1 exon 2 splicing and how the latter may act as a predisposing risk factor for the occurrence of posterior vitreous detachment (PVD)‐associated rhegmatogenous retinal detachment (RRD) in the general population. Using amplification of illegitimate transcripts and allele‐specific minigenes expressed in cultured cells, we demonstrate variability in exon 2 inclusion not only between different control individuals, but also between different COL2A1 alleles. We identify transacting factors that bind to allele‐specific RNA sequences, and investigate the effect of knockdown and overexpression of these factors on exon 2 splicing efficiency. Finally, using a specific cohort of patients with PVD‐associated RRD and a control population, we demonstrate a significant difference in the frequency of the COL2A1 intronic variant rs1635532 between the two groups.